A new genus and other new species of Agraeciini from the Eastern Arc Mountains, East Africa (Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini) - Hemp, Claudia; Ingrisch, Sigfrid; Heller, Klaus-Gerhard (Zootaxa, 2017)
The genus Dendrobia n. gen. is erected to include D. amaniensis n. sp. from the East Usambara Mountains as type species. A second species in this genus, D. octopuncata n. sp., is described from the Udzungwa Mountains of Tanzania. Dendrobia n. gen. is a canopy dweller found only high up on trees in closed submontane and montane forest. The peak frequency of its song is lower than in all other known African Agraeciini, correlating with the large resonant areas in the tegmina. Two new Afroanthracites species, A. ngologolo n. sp. and A. nguru n. sp. are described from the Eastern Arc Mountains in Tanzania. These species are dwellers of understory vegetation in closed forest in the Udzungwa and Nguru Mountains respectively.